Laryngeal Papillomatosis: A Case Report - Mebrouk, Nadia.; Benchidmi, Sara; Hafidi, Naima El; Benbrahim, Fadoua; Jaabouti, Ghizlane; Lamalmi, Najat.; Ayoubi, Ali; Benchekroun, Soumia; Mahraoui, Chafiq (International Journal of Innovative Research in Medical Science, 2022)
Laryngeal papillomatosis (LP) is a relatively rare benign tumoral proliferation of the larynx, usually seen in children. It is due to infection with Human Papilloma Virus (HPV), and the first symptom is chronic dysphonia. There is currently no consensus on the treatment regimen for LP. Several treatments are used, but their efficacy is difficult to determine due to small patient cohorts. In a developing country, the treatment is based on peeling by laryngeal microsurgery. Its capricious evolution requires regular monitoring of patients. The possible prevention through the use of prophylactic vaccines is the most significant recent development. We report the case of a child who was dysphonic and had laryngeal dyspnea, in whom the peeling of a papilloma with forceps under direct laryngoscopy was performed, the histological study affirmed the diagnosis and made it possible to eliminate a neoplasm.